2018
DOI: 10.1186/s41100-018-0157-8
|View full text |Cite
|
Sign up to set email alerts
|

Severe refractory TAFRO syndrome requiring continuous renal replacement therapy complicated with Trichosporon asahii infection in the lungs and myocardial infarction: an autopsy case report and literature review

Abstract: Background: TAFRO (thrombocytopenia, anasarca, fever, reticulin myelofibrosis/renal failure, and organomegaly) syndrome is a systemic inflammatory disorder and unique clinicopathological variant of idiopathic multicentric Castleman disease that was proposed in Japan. Prompt diagnosis is critical because TAFRO syndrome is a progressive and life threating disease. Some cases are refractory to immunosuppressive treatments. Renal impairment is frequently observed in patients with TAFRO syndrome, and some severe ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…Proposed mechanisms include the release of cardio-suppressing mediators and alteration of calcium-phosphate metabolism in inflammation and acute kidney injury. 2,3 In severe sepsis, transmural ischaemia from increased oxygen demand can lead to the hydrolysis of calcium-containing vesicles and calcium influx to myocardial fibres, causing RPLVMC. 2,4,5 This likely explains the electrocardiogram changes and troponin rise in our patients in the absence of obstructive coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…Proposed mechanisms include the release of cardio-suppressing mediators and alteration of calcium-phosphate metabolism in inflammation and acute kidney injury. 2,3 In severe sepsis, transmural ischaemia from increased oxygen demand can lead to the hydrolysis of calcium-containing vesicles and calcium influx to myocardial fibres, causing RPLVMC. 2,4,5 This likely explains the electrocardiogram changes and troponin rise in our patients in the absence of obstructive coronary artery disease.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of SCLS is thought to be the extravasation of fluid and protein from the intravascular to the interstitial space [ 10 ]. Some studies have reported that hypercytokinemia and increased intra-abdominal pressure due to massive ascites caused SCLS in patients with TAFRO syndrome [ 11 ]. Third, PAIgG was positive in this case.…”
Section: Discussionmentioning
confidence: 99%
“…In this report, the patient had a history of alcohol consumption, was diagnosed with intractable ascites associated with liver cirrhosis, and underwent repeated abdominal paracentesis and CART. In a previous study, CART and hemodialysis were reported to be partially effective for TAFRO syndrome, and more than 80% (16/19) of patients with TAFRO syndrome required hemodialysis within 3 weeks of admission ( 10 ). Even if TAFRO syndrome has not been diagnosed, CART and hemodialysis may improve the symptoms.…”
Section: Discussionmentioning
confidence: 99%